Efeitos da leptina e SAA na função de neutrófilos humanos - Silva, Bianca Palmeira Santos da (2020)
Although there is a consensus that the infections incidence is higher in obese, the effect of adipokines on neutrophil function is not completely known. Herein, we hypothesized that leptin and serum amyloid A (SAA) can activate/inactivate neutrophils and interfere with the innate immune response. So, we studied the combined effects of leptin and SAA on the function of human neutrophils. Neutrophils (2.5x106 cells / mL) were isolated and cultured in RPMI medium in the presence and absence of leptin (25 and 50ng/mL), SAA (5ug/mL) and LPS (1ug/mL). In vitro, we analyzed, through flow cytometry technique, the effect of leptin and SAA on parameters related to neutrophil viability; by ELISA we evaluated the release of cytokines (TNF-α, IL-8) and by the chemiluminescence technique amplified by lucigenin we observed the production of ROS. Under the conditions studied, neutrophil treatments with SAA, leptin and the combination SAA and leptin were not toxic to the cells. We observed an increase in ROS production of 60% (*p= 0.01) and 79% (**p= 0.02) by neutrophils, when treated with the combination of SAA and leptin at concentrations of 2.5ng/mL and 25ng/mL respectively. The treatment of neutrophils with leptin at concentrations of 25ng/mL, 50ng/mL and SAA increased by 38% (**p= 0.02) and 92% (***p= 0.003) and 159% (****p= 0.0002) the concentration of TNF-α and these cells, when treated, with leptin at concentrations of 25ng/mL and 50ng/mL with SAA showed an increase of 62% (°p= 0.0044), and 106% (°°°p= 0.0002), respectively. The treatment of neutrophils with leptin at concentrations 25ng / mL and 50ng/mL and SAA increased by 39% (**p= 0.01), 38% (***p= 0.01) and 62% (****p= 0.001) the concentration of IL-8, respectively, and these neutrophils when treated with leptin at a concentration of 50ng / mL with SAA showed an increase of 32% (°p= 0.0001). There was an increase in the production of TNF-α and IL-8 at different concentrations of leptin and in treatments with combined leptin and SAA. Our data indicate that adipose tissue can modulate neutrophil function through adipokine secretion and interfere with the innate immune response.